Theory and practise of State security ministery work - Müller-Enbergs, Helmut (Genocidas ir rezistencija, 1999)
The Ministry of State Security (MSS), in accordance with the resolutions of the Socialist Unity Party of Germany (SED), was obliged to protect the German Democratic Republic (GDR) against external and internal ‘attacks’, to guarantee its territorial integrity and state order, and to prevent possible violations of security interests. The MSS’s primary task was to take action to obtain information on potential harm the GDR politically, economically, socially, or militarily. Several important decrees regulated the recruitment and handling of unofficial staff members. The analysis that follows focuses on the relationship between these normative documents and operations on the ground.
Keywords: Germany; repressive structures; Stasi